Delayed egg introduction beyond infancy and increased egg allergy risk in childhood. (3rd October 2022) - Martone, Giulia M; Lehman, Heather K; Rideout, Todd C; Choudhary, Divya; Cameron, Claire E; Oken, Emily; Rifas‐Shiman, Sheryl L; Camargo, Carlos A; Gold, Diane R; Wen, Xiaozhong
Abstract : Aim: Egg is a major food allergen in childhood. Recent studies suggest that early introduction of allergenic foods can decrease the risk of developing egg allergy. The impact of early egg introduction in the general population is unclear. We examined associations between age of infant egg introduction and childhood egg allergy outcomes in a general population. Methods: The study population consisted of 1217 neonates from Project Viva, a longitudinal pre‐birth cohort in eastern Massachusetts area, USA. Mothers reported age of infant egg introduction and child egg allergy using questionnaires and specific IgE to egg white was assayed. We estimated associations between age of infant egg introduction and egg allergy outcomes using Log‐binomial regression models, adjusting for socio‐demographics and health confounders. Results: Egg allergy at 2 years was significantly higher (8.0% vs. 1.4%, P < 0.0001) in children who had delayed egg introduction beyond infancy, compared with children who were introduced to egg during infancy (adjusted relative risk or aRR 7.58; 95% CI 3.08, 18.61). At 12 years, the risk of egg allergy remained significantly higher (3.9% vs. 1.1%, P = 0.048) in children with delayed egg introduction compared with children introduced to egg during infancy (aRR 4.07; 95% CI 1.20, 13.87). Conclusions: Infants with delayed introduction of eggs after 12 months had increased risk of egg allergy in childhood (2 years) and the relationship persisted in early adolescence (12 years). Our findings suggest that introduction to eggs before 12 months could contribute to the prevention of egg allergy.